An abnormal chamber-like structure after mitral valve replacement. Issue 14 (26th April 2017) - Kang, Yu; Huang, Ritai; He, Ben
Abstract : Clinical introduction: A 59-year-old woman who underwent mitral valve replacement and tricuspid annuloplasty with the De Vega technique without a rigid ring 16 years ago for rheumatic mitral stenosis was referred to our hospital for aggressive dyspnoea and oedema of lower extremities refractory to diuretics. ECG showed atrial fibrillation. Transthoracic echocardiography reveal ed severe tricuspid regurgitation, preserved left and right ventricular systolic function, slightly elevated systolic pulmonary artery pressure and an abnormal chamber-like structure (see online supplementary video A ). Hence, transoesophageal echocardiography (TE) was performed (figure 1, see online supplementary video B ). Question: What is the diagnosis of this abnormal chamber-like structure? Left atrial mass Localised pericardial effusion Left atrial dissection Hiatal hernia Coronary artery aneurysm